Garre′s sclerosing osteomyelitis - Suma R; Vinay C; Shashikanth M; Subba Reddy V (Wolters Kluwer Medknow Publications, 2007)
Garre′s sclerosing osteomyelitis is a specific type of chronic osteomyelitis that mainly affects children and young adults. This disease entity is well-described in dental literature and is commonly associated with an odontogenic infection resulting from dental caries. This paper describes a case of Garre′s osteomyelitis in a 10-year-old boy, in whom the condition arose following pulpoperiapical infection in relation to permanent mandibular right first molar. Clinically the patient presented with bony hard, non-tender swelling and the occlusal radiograph revealed pathognomic feature of "onion skin" appearance. The elimination of periapical infection was achieved by endodontic therapy and the complete bone remodeling was seen radiographically after three months follow-up.